Trends in stroke admissions to a Tanzanian hospital over four decades: a retrospective audit. Issue 10 (1st June 2015) - Walker, Richard W.; Viney, Rachel; Green, Laura; Mawanswila, Manasseh; Maro, Venance P.; Gjertsen, Charlotte; Godfrey, Hannah; Smailes, Rosanna; Gray, William K.
Abstract Aims The aim of this study was to record stroke admissions to a tertiary referral hospital in Tanzania over four decades. Methods We audited the medical records held at a large teaching and tertiary referral hospital in northern Tanzania over four decades. We collected records for the years 1974‐1976, 1984‐1986, 1994‐1995 and 2008. All patients admitted as inpatients with a primary diagnosis of stroke were included in the study. Data collected included age, sex, stroke subtype, predominant side of symptoms and survival to discharge. Results The number of stroke admissions rose from just four in the three‐year period 1974‐1976 (mean 1.3 cases annually) to 153 cases annually in 2008. The mean age of those admitted rose steadily during this period, as did the proportion of females admitted. Conclusions The burden of stroke on health services in Tanzania appears to have increased rapidly. If this increase is to be slowed, then sustainable primary preventative measures to target known stroke risk factors will be required.